The impact of geographic range, sampling, ecology, and time on extinction risk in the volatile clade Graptoloida. Issue 1 (20th December 2016) - Boyle, James; Sheets, H. David; Wu, Shuang-Ye; Goldman, Daniel; Melchin, Michael J.; Cooper, Roger A.; Sadler, Peter M.; Mitchell, Charles E.
Abstract: Although extinction risk has been found to have a consistent negative relationship with geographic range across wide temporal and taxonomic scales, the effect has been difficult to disentangle from factors such as sampling, ecological niche, or clade. In addition, studies of extinction risk have focused on benthic invertebrates with less work on planktic taxa. We employed a global set of 1114 planktic graptolite species from the Ordovician to lower Devonian to analyze the predictive power of species' traits and abiotic factors on extinction risk, combining general linear models (GLMs), partial least-squares regression (PLSR), and permutation tests. Factors included measures of geographic range, sampling, and graptolite-specific factors such as clade, biofacies affiliation, shallow water tolerance, and age cohorts split at the base of the Katian and Rhuddanian stages. The percent variance in durations explained varied substantially between taxon subsets from 12% to 45%. Overall commonness, the correlated effects of geographic range and sampling, was the strongest, most consistent factor (12–30% variance explained), with clade and age cohort adding up to 18% and other factors <10%. Surprisingly, geographic range alone contributed little explanatory power (<5%). It is likely that this is a consequence of a nonlinear relationship between geographic range and extinction risk, wherein the largest reductions in extinction risk are gained from moderate expansion of small geographic ranges. Thus, even large differences in range size between graptolite species did not lead to a proportionate difference in extinction risk because of the large average ranges of these species. Finally, we emphasize that the common practice of determining the geographic range of taxa from the union of all occurrences over their duration poses a substantial risk of overestimating the geographic scope of the realized ecological niche and, thus, of further conflating sampling effects on observed duration with the biological effects of range size on extinction risk.